Off the Waterfront: The Long-run Impact of Technological Change on Dock Workers - Zouheir El-Sahli; Richard Upward (Lund University, School of Economics and Management, Department of Economics, 2015)
We investigate how individual workers and local labour markets adjust over a long time period to a discrete and plausibly exogenous technological shock, namely the introduction of containerisation in the UK port industry. This technology, which was introduced rapidly between the mid-1960s and the late-1970s, had dramatic consequences for specific occupations within the port industry. Using longitudinal micro-census data we follow dock-workers over a 40 year period and examine the long-run consequences of containerisation for patterns of employment, migration and mortality. The results show that the job guarantees protected dock-workers' employment until their removal in 1989. A matched comparison of workers in com- parable unskilled occupations reveals that, even after job guarantees were removed, dock-workers did not fare worse than the comparison group in terms of their labour market outcomes. Our results suggest that job guarantees may significantly reduce the cost to workers of sudden technological change, albeit at a significant cost to the industry.
Keywords: J51; J64; J65; O33; 330; containerisation; labour markets; England and Wales; dock workers; technological change.